The fibroblasts growth factor 21 study in patients with non-alcoholic fatty liver disease and hypertension comorbidities - O. Ya. Babak; K. A. Lapshyna (Zaporožskij Medicinskij Žurnal)
The purpose of the study was to evaluate the fibroblast growth factor 21 levels (FGF-21) in blood plasma and the liver parenchyma state in non-alcoholic fatty liver disease (NAFLD) patients with hypertension.